Radiocarbon analysis reveals expanded diet breadth associates with the invasion of a predatory ant. Issue 1 (December 2017) - Suehiro, Wataru; Hyodo, Fujio; Tanaka, Hiroshi; Himuro, Chihiro; Yokoi, Tomoyuki; Dobata, Shigeto; Guénard, Benoit; Dunn, Robert; Vargo, Edward; Tsuji, Kazuki; Matsuura, Kenji
Abstract Invasions are ecologically destructive and can threaten biodiversity. Trophic flexibility has been proposed as a mechanism facilitating invasion, with more flexible species better able to invade. The termite hunting needle antBrachyponera chinensis was introduced from East Asia to the United States where it disrupts native ecosystems. We show thatB. chinensis has expanded dietary breadth without shifting trophic position in its introduced range. Transect sampling of ants and termites revealed a negative correlation between the abundance ofB. chinensis and the abundance of other ants in introduced populations, but this pattern was not as strong in the native range. Both termite andB. chinensis abundance were higher in the introduced range than in native range. Radiocarbon (14 C) analysis revealed thatB. chinensis has significantly younger 'diet age', the time lag between carbon fixation by photosynthesis and its use by the consumer, in the introduced range than in the native range, while stable isotope analyses showed no change. These results suggest that in the introduced rangeB. chinensis remains a termite predator but also feeds on other consumer invertebrates with younger diet ages such as herbivorous insects. Radiocarbon analysis allowed us to elucidate cryptic dietary change associated with invasion success.